Psychological well-being of individuals after divorce: the role of social support - Anna Kołodziej-Zaleska (Current Issues in Personality Psychology, 2016)
Background Divorce is a transition period in which divorcing individuals face restructuring of the family system and adjustment to changes. The psychological well-being of divorcees can serve as an important indicator of the adjustment process. The achievement of well-being does not come easily for many reasons, one of which is the experience related to a sense of loss associated with the marriage break-up. Social support is a major relational resource for overcoming the crisis and successfully adjusting to post-divorce life.